Propecia cost in australia

$ X = \left( \begin{array}{ccc}
1 & 0 & 0 \\
0 & cos \phi & -sin \phi \\
0 & sin \phi & cos \phi \\
\end{array} \right) $

$ Y = \left( \begin{array}{ccc}
cos \theta & 0 & sin \theta \\
0 & 1 & 0 \\
-sin \theta & 0 & cos \theta \\
\end{array} \right) $

$ Z = \left( \begin{array}{ccc}
cos \psi & -sin \psi & 0 \\
sin \psi & cos \psi & 0 \\
0 & 0 & 1 \\
\end{array} \right) $

$ M = Y * X * Z $

M=\left( \begin{array}{ccc}
cos \theta & 0 & sin \theta \\
0 & 1 & 0 \\
-sin \theta & 0 & cos \theta \\
\end{array} \right)\left( \begin{array}{ccc}
1 & 0 & 0 \\
0 & cos \phi & -sin \phi \\
0 & sin \phi & cos \phi \\
\end{array} \right) \left( \begin{array}{ccc}
cos \psi & -sin \psi & 0 \\
sin \psi & cos \psi & 0 \\
0 & 0 & 1 \\
\end{array} \right)$

M=\left( \begin{array}{ccc}
cos \theta & 0 & sin \theta \\
0 & 1 & 0 \\
-sin \theta & 0 & cos \theta \\
\end{array} \right) \left( \begin{array}{ccc}
cos \psi & -sin \psi & 0 \\
cos \phi sin \psi & cos \phi cos \psi & -sin \phi \\
sin \phi sin \psi & sin \phi cos \psi & cos \phi \\
\end{array} \right) $

M=\left( \begin{array}{ccc}
cos \theta cos \psi + sin \theta sin \phi sin \psi &
-cos \theta sin \psi + sin \theta sin \phi cos \psi &
sin \theta cos \phi \\
cos \phi sin \psi &
cos \phi cos \psi &
-sin \phi \\
-sin \theta cos \psi + cos \theta sin \phi sin \psi &
sin \theta sin \psi + cos \theta sin \phi cos \psi &
cos \theta cos \phi \\
\end{array} \right)$

\begin{alignat*}{3}
\phi &= asin(sin \phi) &&= asin(-M_{c2,r1}) \\
\theta &= atan(\frac{sin \theta}{cos \theta}) &&= atan(\frac{M_{c2,r0}}{M_{c2,r2}}) \\
\psi &= atan(\frac{sin \psi}{cos \psi}) &&= atan(\frac{M_{c0,r1}}{M_{c1,r1}})\\
\end{alignat*}

\begin{flalign*}
sin \phi &= 1 \\
cos \phi &= 0 \\
\end{flalign*}

M=\left( \begin{array}{ccc}
cos \theta cos \psi + sin \theta sin \psi &
-cos \theta sin \psi + sin \theta cos \psi &
0 \\
0 &
0 &
-1 \\
-sin \theta cos \psi + cos \theta sin \psi &
sin \theta sin \psi + cos \theta cos \psi &
0 \\
\end{array} \right)$

\begin{flalign*}
sin (\psi - \theta) &= cos \theta sin \psi - sin \theta cos \psi \\
cos (\psi - \theta) &= cos \theta cos \psi + sin \theta sin \psi \\
\end{flalign*}

M=\left( \begin{array}{ccc}
cos(\psi - \theta) & -sin(\psi - \theta) & 0 \\
0 & 0 & -1 \\
sin(\psi - \theta) & cos(\psi - \theta) & 0 \\
\end{array} \right)$

\begin{alignat*}{3}
\phi &= asin(1) &&= \frac{\pi}{2} \\
\theta &= 0 &&= 0 \\
\psi &= atan(\frac{sin \psi}{cos \psi}) &&= atan(\frac{-M_{c1,r0}}{M_{c0,r0}}) \\
\end{alignat*}

\begin{flalign*}
sin \phi &= -1 \\
cos \phi &= 0 \\
\end{flalign*}

M=\left( \begin{array}{ccc}
cos \theta cos \psi - sin \theta sin \psi &
-cos \theta sin \psi - sin \theta cos \psi &
0 \\
0 &
0 &
1 \\
-sin \theta cos \psi - cos \theta sin \psi &
sin \theta sin \psi - cos \theta cos \psi &
0 \\
\end{array} \right)$

\begin{flalign*}
sin (\psi + \theta) &= cos \theta sin \psi + sin \theta cos \psi \\
cos (\psi + \theta) &= cos \theta cos \psi - sin \theta sin \psi \\
\end{flalign*}

M=\left( \begin{array}{ccc}
cos(\psi + \theta) & -sin(\psi + \theta) & 0 \\
0 & 0 & 1 \\
-sin(\psi + \theta) & -cos(\psi + \theta) & 0 \\
\end{array} \right)$

\begin{alignat*}{3}
\phi &= asin(-1) &&= -\frac{\pi}{2} \\
\theta &= 0 &&= 0 \\
\psi &= atan(\frac{sin \psi}{cos \psi}) &&= atan(\frac{-M_{c1,r0}}{M_{c0,r0}}) \\
\end{alignat*}